Inquérito sorológico para hanseníase em profissionais de saúde no Hospital Universitário Cassiano Antonio Moraes - Vitória - Espírito Santo - Brasil - Landeiro, Luana Gomes (2014)
Background: Leprosy is a major public health problem in Brazil, and the control programs that aim to break the chain of transmission are focused on household contact of leprosy patients. However, the importance of contact outside the home and from individuals with subclinical infections are being studied more than ever before. Health professionals, in addition to being placed in the same endemic context of their patients, come into contact, often recursively, to leprosy patients. Objective: To better understand health professional exposure levels of Mycobacterium leprae at the Cassiano Antonio Moraes University Hospital, by way of determining their PGL I seropositivity and the correlation of this seropositivity to several factors, such as gender, occupation, place of work, time of practice, working with leprosy patients, presence of household contact with leprosy, comorbidities related to false positive ML-Flow and consumption of beef, milk and related products. Patients and Methods: Cross-sectional, descriptive, observational and homodemic study methods using a sample of 300 health professionals from the Cassiano Antonio Moraes University Hospital. Results: Of the 300 health professionals recruited, 296 had valid ML Flow tests and were therefore included in the study. Of these 296 health professionals studied, 83 % were female, 59 % were nursing assistants, 22 % were physicians, 5 % worked in leprosy clinics, 71 % had their professions for more than ten years old, 79 % denied having worked with leprosy patients and 7 % reported household contact with leprosy. The PGL I seropositivity among participants was 30.7 %. Discussion and Conclusion: In addition to the high PGL I seropositivity identified among the health professionals studied, statistical analysis determined a significant association (p = 0.001) between positivity for anti-PGL-I and the presence of household contact with leprosy patients. We could not demonstrate an association between anti -PGL I positivity and the other factors analyzed.